Development of Receptor Binding Domain (RBD)‐Conjugated Nanoparticle Vaccines with Broad Neutralization against SARS‐CoV‐2 Delta and Other Variants. Issue 11 (10th February 2022) - Chen, Ran; Zhang, Xiantao; Yuan, Yaochang; Deng, Xiaohui; Wu, Bolin; Xi, Zhihui; Wang, Guanwen; Lin, Yingtong; Li, Rong; Wang, Xuemei; Zou, Fan; Liang, Liting; et al.
Abstract: The SARS‐CoV‐2 Delta (B.1.617.2) strain is a variant of concern (VOC) that has become the dominant strain worldwide in 2021. Its transmission capacity is approximately twice that of the original strain, with a shorter incubation period and higher viral load during infection. Importantly, the breakthrough infections of the Delta variant have continued to emerge in the first‐generation vaccine recipients. There is thus an urgent need to develop a novel vaccine with SARS‐CoV‐2 variants as the major target. Here, receptor binding domain (RBD)‐conjugated nanoparticle vaccines targeting the Delta variant, as well as the early and Beta/Gamma strains, are developed. Under both a single‐dose and a prime‐boost strategy, these RBD‐conjugated nanoparticle vaccines induce the abundant neutralizing antibodies (NAbs) and significantly protect hACE2 mice from infection by the authentic SARS‐CoV‐2 Delta strain, as well as the early and Beta strains. Furthermore, the elicitation of the robust production of broader cross‐protective NAbs against almost all the notable SARS‐CoV‐2 variants including the Omicron variant in rhesus macaques by the third re‐boost with trivalent vaccines is found. These results suggest that RBD‐based monovalent or multivalent nanoparticle vaccines provide a promising second‐generation vaccine strategy for SARS‐CoV‐2 variants. Abstract : Receptor binding domain (RBD)‐conjugated nanoparticle vaccines are developed with broad neutralization against SARS‐CoV‐2 Delta and other variants. There is a robust production of broader cross‐protective NAbs against almost all the notable SARS‐CoV‐2 variants including the Omicron in rhesus macaques by the third re‐boost with trivalent vaccines. These multivalent nanoparticle vaccines might be a promising second‐generation vaccine for SARS‐CoV‐2 variants.